An examination of public attitudes and behaviour towards waste management: the case of Galway - Fahy, Frances (Trinity College (Dublin, Ireland). Department of Geography, 2006)
An examination of public attitudes and behaviour towards waste management: The case of Galway. In recent years waste and general environmental issues have become an area of prime concern for national governments, policymakers and local communities. However, research on waste management has largely ignored the role of individual attitudes and actions, preferring to concentrate on technical or scientific solutions to waste management problems. Many of the waste management policies adopted in Ireland focus on the provision of information about waste and the environment in general with the assumption that the public will absorb this information and change their behaviour accordingly. However, this thesis proposes that waste management behaviour is affected by more than just information and that a gap (commonly referred to as the value-action gap) exists between individuals’ attitudes and actions towards waste.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin